La Gestión en el proceso de recuperación de cartera vencida y su incidencia en la rentabilidad de la cooperativa de ahorro y crédito Educadores de Napo ltda., del cantón Tena provincia de napo período2017 - Carrillo Unapucha, Grimaldi Fernando (2019)
The following work emphasizes: The management in the process of recovery of overdue portfolio and its impact on the profitability of the Saving and Credit Educators cooperative of Napo Ltda., Of the Canton Tena Napo Province, 2017 period, with the purpose of incorporating the administrative management for the improvement of the organizational development of the Cooperativa de Ahorro y Credito Educadores de Napo. The investigation is constituted by four chapters, the same that are developed next: The first chapter is composed of the referential framework, which integrates the approach to the problem, formulation of the problem, chapter two limits the general objective and specific objectives. Then in the third chapter, which is made up of a theoretical framework, which contains background and the theoretical foundation, together it covers the generalities of the cooperative, past due portfolio and finally with regard to profitability. The fourth chapter details the methods used for the present investigation, the type of research, the design of the research, the population and sample, the techniques and instruments for gathering information, the processing of information, in the fifth chapter performs the analysis and interpretation of results. The sixth chapter is composed of the conclusions and recommendations of the investigation to show the current situation of the portfolio and its impact on the profitability of the institution